Autonomía e independencia en el Río de la Plata, 1808-1810 - Chiaramonte, José Carlos (El Colegio de México, A.C., 2008)
This work seeks to reveal the aim of those participating in the River Plate independence movement, and how they legitimated the establishment of local governments. The  author  explains how political legitimacy was based on the doctrine of “retro version of sovereignty to the people”, and on the principle of consent, core of the contractual conceptions typical  of natural law, and how this sovereignty  was assumed by the viceroyalty's “principal  cities”, since there  didn't exist then  “a” people,  but fourteen  “American  peoples”.  He  also explains how  in its origins the “May Revolution” was not an independence movement, nor a result of a previous plan, but an audacious decision of the “American  Spaniards”  —supported by  some  peninsular  Spaniards— to take control of the events produced by the monarchical crisis.